The Use of Robots in Hydrography - Kerr, A. J.; Dinn, D. F. (The International Hydrographic Review, 2015)
Robots are increasingly being applied to tasks which are hazardous or which they can carry out more effectively or safely than people. The use of remotely controlled submersibles for conducting precise undersea surveys has been proposed recently in conjunction with oil industry activities. In Canada robot vehicles are currently under development for offshore surveys of areas under permanent ice cover. This paper describes two requirements, the different technology that is involved in each system, and the progress to date on the developments which, in the case of one system, have now advanced to successful field trials.